TEACHING KNOWLEDGE AND KNOWLEDGE IN THE CONTINUING EDUCATION OF TEACHERS WHO TEACH MATHEMATICS IN THE EARLY YEARS: IN THE LIGHT OF THE THEORIES OF TARDIF, SHULMAN AND PIMENTA - Aparecida da Silva, Renata; Maria Pontin Darsie, Marta (Revista Gênero e Interdisciplinaridade, 2024)
The subject of this article is teaching knowledge and the continuing education of teachers who teach mathematics in the early years of elementary school, and the guiding question is: what are the contributions of the theories of Tardif, Shulman and Pimenta to the understanding of teaching knowledge for the continuing education of teachers who teach mathematics in the early years? The aim is to analyze the literature on teaching knowledge and knowledge necessary for the practice of continuing education for teachers who teach mathematics in the early years of elementary school, based on theories of teaching knowledge and the reflective teacher. The research is based on a qualitative, interpretative bibliographical approach, based on the works of the authors Tardif (2014), Shulman (1986) and Pimenta (1999), which provide comprehensive perspectives on teaching practice, professional identity, teacher training and the different types of knowledge involved. The conclusion is that it is important to understand the definition of teaching knowledge and its articulation with the continuing education of teachers who teach mathematics in the early years. This subject is complex and multifaceted, as it requires a theoretical and methodological approach that takes into account the cognitive, psychological, curricular, pedagogical, social, historical and cultural dimensions linked to the process of teaching and learning mathematics. It is therefore necessary for both teacher educators and future teacher educators to reflect on their training, their professional identity and their teaching practice.